Higher 25(OH)D(2) Is Associated With Lower 25(OH)D(3) and 1,25(OH)(2)D(3) - Swanson, Christine M. (Endocrine Society, 2014)
CONTEXT: Despite common use of supplemental vitamin D(2) in clinical practice, the associations of serum vitamin D(2) concentrations with other vitamin D metabolites and total vitamin D are unclear. OBJECTIVE: The aim of the study was to measure vitamin D(2) and D(3) levels and examine their associations with each other and with total vitamin D. DESIGN: We performed a cross-sectional analysis of 679 randomly selected participants from the Osteoporotic Fractures in Men Study. 25-Hydroxyvitamin D(2) [25(OH)D(2)], 25(OH)D(3), 1,25-dihydroxyvitamin D(2) [1,25(OH)(2)D(2)], and 1,25(OH)(2)D(3) were measured using liquid chromatography-tandem mass spectrometry and were summed to obtain total 25(OH)D and 1,25(OH)(2)D. Associations between all metabolites (D(2), D(3), and total levels) were examined using Wilcoxon rank-sum tests and Spearman correlations. RESULTS: 25(OH)D(2) and 1,25(OH)(2)D(2) were detectable in 189 (27.8%) and 178 (26.2%) of the men, respectively. Higher 25(OH)D(2) levels did not correlate with higher total 25(OH)D (r = 0.10; P = .17), although median total 25(OH)D was slightly higher in those with detectable vs undetectable 25(OH)D(2) (25.8 vs 24.3 ng/mL; P < .001). 25(OH)D(2) was not positively associated with total 1,25(OH)(2)D levels (r = −0.11; P = .13), and median 1,25(OH)(2)D level was not higher in those with detectable vs undetectable 25(OH)D(2). Higher 25(OH)D(2) was associated with lower 25(OH)D(3) (r = −0.35; P < .001) and 1,25(OH)(2)D(3) (r = −0.32; P < .001), with median levels of both D(3) metabolites 18–35% higher when D(2) metabolites were undetectable. CONCLUSIONS: In a cohort of older men, 25(OH)D(2) is associated with lower levels of 25(OH)D(3) and 1,25(OH)(2)D(3), suggesting that vitamin D(2) may decrease the availability of D(3) and may not increase calcitriol levels.